Design and development of biometric-based techniques for e-security - Tham, Eliza Li Xin (2015)
Over the years, technologies have become so advanced and developed that most users prefer to shop online rather than visiting the brick and mortar store due to the convenience of making purchases on the e-Commerce application, anytime and anywhere. Most e-Commerce application consists of a typical one layer authentication whereby user login via their registered username and password which is insufficient as information could be stolen. Therefore it is important to integrate a multi-layer authentication method into the e-Commerce application to improve the security. As most biometric features are unique and could not be stolen from individual, the various biometric-based technologies will be a good alternative to integrate as the multi-layer authentication. The various biometric-based technologies have been identified and the most suitable technology will be chosen. The proposed biometric-based technique, face recognition method would be integrated into the existing e-Commerce application using the Principal Component Analysis (PCA) algorithm. The result of the face recognition using the PCA algorithm shows a certain level of both success and failure rate due to certain factors. Future works are recommended to improve both the integration of e-Commerce application and the face recognition system used.